Independent Recruitment of Different Types of Phospholipases A2 to the Venoms of Caenophidian Snakes: The Rise of PLA2-IIE within Pseudoboini (Dipsadidae) - Bayona-Serrano, Juan (2023)
Snake venoms harbor a wide and diverse array of enzymatic and nonenzymatic toxic components, allowing them to exert myriad effects on their prey. However, they appear to trend toward a few optimal compositional scaffolds, dominated by four major toxin classes: SVMPs, SVSPs, 3FTxs, and PLA2s. Nevertheless, the latter appears to be restricted to vipers and elapids, as it has never been reported as a major venom component in rear-fanged species. Here, by investigating the original transcriptomes from 19 species distributed in eight genera from the Pseudoboini tribe (Dipsadidae: Xenodontinae) and screening among seven additional tribes of Dipsadidae and three additional families of advanced snakes, we discovered that a novel type of venom PLA2, resembling a PLA2-IIE, has been recruited to the venom of some species of the Pseudoboini tribe, where it is a major component. Proteomic and functional analyses of these venoms further indicate that these PLA2s play a relevant role in the venoms from this tribe. Moreover, we reconstructed the phylogeny of PLA2s across different snake groups and show that different types of these toxins have been recruited in at least five independent events in caenophidian snakes. Additionally, we present the first compositional profiling of Pseudoboini venoms. Our results demonstrate how relevant phenotypic traits are convergently recruited by different means and from homologous and nonhomologous genes in phylogenetically and ecologically divergent snake groups, possibly optimizing venom composition to overcome diverse adaptative landscapes.